ANALISIS QS. AN-NAHL AYAT 66: PEMANFAATAN SUSU SAPI UNTUK KESEHATAN HOLISTIK DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Asyafa, Mila Khansya Asyafa; Salsabila, Alshafa; Fauzi, Dimas; Salmah Febriani, Ina (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
This research examines the utilization of cow's milk for holistic health based on the analysis of QS. An-Nahl verse 66. The main focus of the research is the importance of maintaining health through good consumption patterns, with an emphasis on reducing the consumption of sugary foods and drinks that are at risk of causing non-communicable diseases (NCDs) such as diabetes and diabetes. Risk of causing non-communicable diseases (NCDs) such as diabetes and obesity. Data shows the high consumption of sugary drinks in Indonesia which contributes to the increasing number of people with diabetes. As a healthy alternative, whole cow's milk is proposed to help stabilize blood sugar and reduce dependence on sugary drinks. Through a qualitative approach, the authors gathered data from the Qur'an, literature, and interviews to support the argument that cow's milk has significant health benefits. In addition, the article highlights the harmony between Islamic principles and modern health science, despite challenges such as cow's milk allergy and low local milk production. This research emphasizes the importance of utilizing cow's milk in a healthy lifestyle and encourages further research on the health and economic impacts of cow's milk consumption. Thus, cow's milk is not only seen as a source of nutrition, but also as part of worship and gratitude to Allah.